Manual de clasificación de puestos para el Gobierno Autónomo Descentralizado Municipal del cantón La Maná - Cevallos Bravo, Erika Patricia (2013)
In Ecuador, several autonomous decentralized municipal governments present conflicts in administration, public management, quality of care and other services, product of poor administrative control and implementation of mechanisms governing the management of human talent. Despite the fact that there are legal provisions contained in the law of administrative regime, nowadays many public entities are not considering any regulation for the classification of posts governing the involvement of employees, which has caused labor demotivation and dissatisfaction with the work carried out; this contributes to labor inefficiency and institutional commitment of the employees. It is significant that municipal entities possess tools that streamline the administrative management of the human; by such talent reason drafted a Manual of Job Classification for Municipal GAD of canton La Maná, according to LOSEP, setting standards for classification processes, based on the analysis, description and assessment of the competence of applicants for the post. To implement the field study, used various techniques and research instruments, which made possible the collection, interpretation and analysis of the results achieved through the application of interviews and surveys, respectively 8 municipal representatives, 8 area directors and 111 employees of decentralized self-government Municipal of canton La Maná. The analysis of the results of the field study allowed to verify the hypothesis "with the elaboration of the manual of classification of posts will be grouping the decentralized Municipal self-government of canton La Maná jobs based on the complexity of the tasks and responsibilities of each one of its officials", stating that with the development of the manual and grouping of jobs administrative and technical processes of employees working in different areas of the Municipal institution will obviously be improved. The purpose of the manual is to optimize organizational and functional development of the Municipal GAD of canton La Maná. This is justified on the need to classify and bring jobs, in order to set objectives, roles and responsibilities, according to the complexity of the tasks and responsibilities of each one of its officials. With this important administrative tool, you can optimize the organizational and operational performance of human talent, will also allow instruct staff, taking care to minimize the ineffectiveness of the collaborators, the shortcomings that arise in the administrative and operational development will also decrease.